Outcome Measures After Shoulder Stabilization in the Athletic Population: A Systematic Review of Clinical and Patient-Reported Metrics. Issue 9 (16th September 2020) - Fanning, Edel; Maher, Natasha; Cools, Ann; Falvey, Eanna C.
Background: Athletic endeavor can require the "athletic shoulder" to tolerate significant load through supraphysiological range and often under considerable repetition. Outcome measures are valuable when determining an athlete's safe return to sport. Few data are available to guide a clinician's choice from the variety of measures available. Purpose: To describe the use of quantifiable objective outcome measures and patient-reported outcome tools after glenohumeral joint stabilization, specifically in an athletic population. The secondary aim of our study was to assess whether the method of measurement used was clearly described and standardized to aid clinical interpretation. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic search of MEDLINE, Scopus, SPORTDiscus, and Web of Science databases was performed in December 2018 based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. After the application of selection criteria, a full review of identified papers, and screening of reference lists, a total of 62 studies were included in the review. All studies were independently appraised for quality, predefined data fields were populated and cross-checked for accuracy, and results were then summarized from these data fields. Results: Of the 62 included studies, 94% used a quantifiable objective clinical outcome. A majority (85%) of the studies measured range of motion, 21% recorded muscle strength, 5% measured electromyographic activity, 5% examined shoulder kinematics, and 3% assessed joint proprioception after surgery. However, only 18% of the studies clearly described a standardized method of measuring the outcome. Nearly all (95%) of the studies used at least 1 patient-reported outcome measure. The Rowe score was most commonly used (35%). Conclusion: We must standardize and clearly describe the use of quantifiable objective outcome measures to aid clinical interpretation. A concerted effort should also be made to standardize the use of patient-reported outcome tools after shoulder stabilization in the athletic population.